Pigs, Cows, and Boarders: Non-Wage Forms of Survival among Montreal Families, 1861-91 - Bradbury, Bettina (Labour / Le Travail, 1984)
To understand the family economy of the working class in the period of early industrial capitalism it is necessary to go beyond a simple consideration of the sufficiency of wages, to put aside the equation of work with wage labour and to examine other ways in which survival could be enhanced. This paper begins an examination of non-wage-based survival strategies. It focuses on animal raising, gardening, the taking in of boarders and house sharing in mid- to late-nineteenth-century Montreal. These particular survival strategies can be ascertained to some extent from people's responses to the census taker. Analysis of their responses as found in the manuscript schedules of 1861 and 1871 constitutes the core of the paper. Professionals and proprietors were most likely to keep cows, the semi- and unskilled pigs. Pigs were outlawed in this period, while cows remained legal. Gardening, too, was largely eliminated on the narrow, densely built lots of the working class. The outlawing of pigs represents one of a complex of changes that, over the length of a generation, severely curtailed the proletariat's access to means of supplementing their wages and altered the contributions a wife and children could make to the family economy.